PROBLEM PENENTUAN KARIR ALUMNI PRODI BIMBINGAN KONSELING ISLAM DI KOTA PADANGSIDIMPUAN - Faisal Akbar Manurung; Wahidah Fitriani (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
The background of this research problem is the problem of determining the careers of alumni of the 2012 batch of Islamic Counseling Study Program in Padangsidimpuan City. The problem in this research is that many alumni of the Islamic Counseling Study Program still work not according to their competence with the BKI profile. Based on the above background, the aim of this research is to find out the problems of alumni of Islamic Counseling Study Program class of 2012, and to find out what problems alumni of Islamic Counseling Study Program class of 2012 have in determining their careers that are not in accordance with competence. This research uses qualitative research methods, based on the type of research is descriptive qualitative research. The subjects in this study were alumni of the Islamic Counseling Study Program, Faculty of Da'wah and Communication Studies class of 2012. Data collection instruments used in this study consisted of interviews, observation, and documentation. Based on the research results, it is known that many alumni of Islamic Counseling Study Program work not in accordance with the profile of Islamic Counseling Guidance who can work as Counselors in social institutions (Clergy) in Hospitals, Religious Counselors, Preachers, HR Development Motivators, Bintal Workers in Police and Abri. This is due to the problems that alumni have.